American Artists Paint the City: Katharine Kuh, the 1956 Venice Biennale, and New York’s Place in the Cold War Art World - Simpson, Mary Caroline (American Studies, 2010)
By 1956, Alfred Barr and the Museum of Modern Art (MoMA), which then owned the American Pavilion, had recognized the cold war utility of the Venice Biennale. Relying on Clement Greenberg’s formalism, it promoted Abstract Expressionism as the culmination of a European-inspired, American-produced aesthetic embodying universal values with the hope of winning over the moderate European left. American Artists Paint the City, an exhibition for the 1956 Venice Biennale momentarily complicated this agenda. Guest curator Katharine Kuh of the Art Institute of Chicago organized an innovative exhibition thematically uniting 20th century American modernist painters. Her presentation of Jackson Pollock and Willem de Kooning as the inheritors of a New World modernist heritage elicited powerful opposition from American art authorities supporting lineage ties to international modernism as well as upset observers abroad who saw it as a chauvinistic and pretentious effort to undermine European ascendancy in the transatlantic art world. An examination of these reactions exposes the importance of institutional politics in shaping canonical aesthetic priorities and sheds light on the intersecting roles of critics, curators, artists, and patrons in the construction of accepted traditions.